2001
DOI: 10.1051/0004-6361:20011100
|View full text |Cite
|
Sign up to set email alerts
|

MHD consistent cellular automata (CA) models

Abstract: Abstract.In Isliker et al. (2000b), an extended cellular automaton (X-CA) model for solar flares was introduced. In this model, the interpretation of the model's grid-variable is specified, and the magnetic field, the current, and an approximation to the electric field are yielded, all in a way that is consistent with Maxwell's and the MHD equations. The model also reproduces the observed distributions of total energy, peak-flux, and durations. Here, we reveal which relevant plasma physical processes are imple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
19

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(123 citation statements)
references
References 25 publications
4
100
0
19
Order By: Relevance
“…of all sizes that follow a well defined statistical law [30,31,32], which agrees remarkably well with the observed flare statistics [33]. We can then conclude, after many years of studies, that a possible model for the dynamic evolution of the AR is the following: The 3D magnetic field is stressed from the photospheric motions, forms continuously UCS which relax, re-arranging the local magnetic field and causing flares of all sizes (Fig.…”
Section: Energy Release and Particle Acceleration In Complex Magneticsupporting
confidence: 81%
See 1 more Smart Citation
“…of all sizes that follow a well defined statistical law [30,31,32], which agrees remarkably well with the observed flare statistics [33]. We can then conclude, after many years of studies, that a possible model for the dynamic evolution of the AR is the following: The 3D magnetic field is stressed from the photospheric motions, forms continuously UCS which relax, re-arranging the local magnetic field and causing flares of all sizes (Fig.…”
Section: Energy Release and Particle Acceleration In Complex Magneticsupporting
confidence: 81%
“…A stochastic model for type III bursts was introduced and compared with observations [42]. In this model the AR is assumed inhomogeneous with a very large number of fragmented energy release regions (UCSs) connected to magnetic fibers.…”
Section: Dcm Spikes Type III Burstsmentioning
confidence: 99%
“…The physical reason for selecting this criterion lies in the fact that large magnetic stresses favor magnetic reconnection in three dimensions, even in the absence of null points (Priest et al 2003). Mathematically, it can be shown that the selection of G av as the critical quantity in our model relates to the diffusive term of the induction equation (see Isliker et al 1998, for a detailed discussion). Let us write the induction equation in the form:…”
Section: "Disco": a Module To Identify Magnetic-field Instabilitiesmentioning
confidence: 99%
“…The simulation results presented in the next section have been performed using a 32 × 32 × 32 cubic grid with "open" boundaries in the relaxation events (see Isliker et al 2001, for a detailed discussion on open boundary conditions). Each simulation is driven for 3 × 10 5 iterations, which equals the times that LOAD module is being called during the simulation.…”
Section: Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation